Characterization of gana-1, a Caenorhabditis elegans gene encoding a single ortholog of vertebrate alpha-galactosidase and alpha-N-acetylgalactosaminidase - Hujová, Jana; Sikora, Jakub; Dobrovolný, Robert; Poupetová, Helena; Ledvinová, Jana; Kostrouchová, Marta; Hrebícek, Martin (BMC cell biology, 2005)
BACKGROUND: Human alpha-galactosidase A (alpha-GAL) and alpha-N-acetylgalactosaminidase (alpha-NAGA) are presumed to share a common ancestor. Deficiencies of these enzymes cause two well-characterized human lysosomal storage disorders (LSD)--Fabry (alpha-GAL deficiency) and Schindler (alpha-NAGA deficiency) diseases. Caenorhabditis elegans was previously shown to be a relevant model organism for several late endosomal/lysosomal membrane proteins associated with LSDs. The aim of this study was to identify and characterize C. elegans orthologs to both human lysosomal luminal proteins alpha-GAL and alpha-NAGA. RESULTS: BlastP searches for orthologs of human alpha-GAL and alpha-NAGA revealed a single C. elegans gene (R07B7.11) with homology to both human genes (alpha-galactosidase and alpha-N-acetylgalactosaminidase)--gana-1. We cloned and sequenced the complete gana-1 cDNA and elucidated the gene organization.Phylogenetic analyses and homology modeling of GANA-1 based on the 3D structure of chicken alpha-NAGA, rice alpha-GAL and human alpha-GAL suggest a close evolutionary relationship of GANA-1 to both human alpha-GAL and alpha-NAGA. Both alpha-GAL and alpha-NAGA enzymatic activities were detected in C. elegans mixed culture homogenates. However, alpha-GAL activity on an artificial substrate was completely inhibited by the alpha-NAGA inhibitor, N-acetyl-D-galactosamine.A GANA-1::GFP fusion protein expressed from a transgene, containing the complete gana-1 coding region and 3 kb of its hypothetical promoter, was not detectable under the standard laboratory conditions. The GFP signal was observed solely in a vesicular compartment of coelomocytes of the animals treated with Concanamycin A (CON A) or NH4Cl, agents that increase the pH of the cellular acidic compartment. Immunofluorescence detection of the fusion protein using polyclonal anti-GFP antibody showed a broader and coarsely granular cytoplasmic expression pattern in body wall muscle cells, intestinal cells, and a vesicular compartment of coelomocytes.Inhibition of gana-1 by RNA interference resulted in a decrease of both alpha-GAL and alpha-NAGA activities measured in mixed stage culture homogenates but did not cause any obvious phenotype. CONCLUSIONS: GANA-1 is a single C. elegans ortholog of both human alpha-GAL and alpha-NAGA proteins. Phylogenetic, homology modeling, biochemical and GFP expression analyses support the hypothesis that GANA-1 has dual enzymatic activity and is localized in an acidic cellular compartment.
Keywords: molekulární evoluce; sekvenční seřazení; alfa-N-acetylgalaktosaminidasa; alpha-N-Acetylgalactosaminidase; Lysosomes; Humans; sekvence nukleotidů; Phylogeny; proteiny; Sequence Analysis, DNA; Molecular Sequence Data; klonování DNA; sekvenční homologie nukleových kyselin; molekulární sekvence - údaje; Evolution, Molecular; Proteins; alfa-galaktosidasa; lidé; zvířata; Caenorhabditis elegans Proteins; Structural Homology, Protein; sekvenční analýza DNA; proteiny Caenorhabditis elegans; alpha-Galactosidase; Base Sequence; fylogeneze; Sequence Homology, Nucleic Acid; strukturní homologie proteinů; lyzozomy; Animals; Cloning, Molecular; Sequence Alignment